2022
DOI: 10.1136/bmjopen-2021-059661
|View full text |Cite
|
Sign up to set email alerts
|

Using nasal sprays to prevent respiratory tract infections: a qualitative study of online consumer reviews and primary care patient interviews

Abstract: ObjectivesNasal sprays could be a promising approach to preventing respiratory tract infections (RTIs). This study explored lay people’s perceptions and experiences of using nasal sprays to prevent RTIs to identify barriers and facilitators to their adoption and continued use.DesignQualitative research. Study 1 thematically analysed online consumer reviews of an RTI prevention nasal spray. Study 2 interviewed patients about their reactions to and experiences of a digital intervention that promotes and supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…be available on request). The digital intervention to support nasal spray use and its development is described in more detail elsewhere [28].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…be available on request). The digital intervention to support nasal spray use and its development is described in more detail elsewhere [28].…”
Section: Plos Onementioning
confidence: 99%
“…We accepted that this would provide less power for our key secondary outcome (incidence of infections). However, the aim for the latter outcome is to compare each intervention with control, so using the arguments of Cook and Farewell, since each analysis of intervention versus control is independent, this should not require a conservative Bonferroni correction [28], and we can use an alpha of 0.05. Using these assumptions, the above sample size would provide more than 80% power to estimate a 25% reduction in the incidence of infections from 20% to 15% in each stratum and more than 90% power if the incidence of infections is 15% using all strata combined.…”
Section: Provisional Sample Size Calculation Agreed With the Funder F...mentioning
confidence: 99%
“…Nasal spray pumps, celebrated for their non-invasive, efficient, and patient-compliant method of delivering a wide range of medications, are expanding beyond traditional uses like treating nasal allergies and the common cold to encompass a broader spectrum of therapeutic applications [1,2]. This includes serving as a practical approach for the topical management of conditions affecting the nose and paranasal sinuses, such as both forms of rhinitis and sinusitis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are not expensive, can be stored/shipped at room temperature, and are used in a self-administration manner without the requirement of healthcare staff and medical facility. A study ( Williamson et al, 2022 ) based on online customer survey showed that lay people who are vulnerable to RTIs have strong intentions to use a nasal spray during the COVID-19 pandemic. Recently, the German Society of Hospital Hygiene has included virucidal nasal sprays and mouthwash solutions as supplemental control measures against SARS-CoV-2 infection in its guidelines ( Kramer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%